Association between medication adherence and disease outcomes in patients with hepatitis B-related cirrhosis: a population-based case–control study - Vivian Chia-Rong Hsieh; Kuo-Yu Fu; Meng-Lun Hsieh; Jou-An Chen (BMJ Open)
Objective To evaluate medication adherence among patients with hepatitis B-related cirrhosis who developed decompensation and mortality, and to examine the association between medication adherence and patients’ disease outcomes.Design In this retrospective case–control study, patients aged over 20 years old and diagnosed with both chronic hepatitis B and cirrhosis from 2007 to 2016 are identified using a population-based medical claims database. Two prognosis endpoints (decompensation and mortality) are used, respectively, to classify subjects into two different case–control sets. Study groups are propensity-score matched. Medication possession ratio (MPR) is used as a measure of treatment adherence for oral antiviral drugs, and conditional logistic regression models are used to estimate the odds of decompensation and mortality after accounting for MPR and other covariates.Results Between decompensated and compensated patients, longer term treatment adherence is seen higher in the compensated group versus the decompensated group: 1-year MPR (0.65±0.43 vs 0.57±0.53) and 6-month MPR (0.79±0.52 vs 0.76±0.79). On the contrary, 3-month adherence is higher in the decompensated group (1.00±1.15 vs 0.96±0.79). For patients with and without mortality, drug adherence is ubiquitously higher in the alive group regardless of follow-up length: 1-year MPR (0.62±0.44 vs 0.50±0.51), 6-month MPR (0.78±0.62 vs 0.69±0.72) and 3-month MPR (0.97±0.91 vs 0.96±1.12). After accounting for confounding variables, we find that the likelihood of complicated cirrhosis is significantly lower in more adherent patients and the benefit increases with more persistent adherence (log 1-year MPR OR: 0.75, 95% CI: 0.73 to 0.77). Similar results are observed for the adjusted likelihood of mortality (log 1-year MPR OR: 0.70, 95% CI: 0.68 to 0.72).Conclusions Long-term patient adherence to oral antiviral therapy remains inadequate in patients with hepatitis B virus-related cirrhosis. Their adherence to oral antiviral therapy appears to be inversely associated with decompensation and mortality.